Stability of the demand for M1 and harmonized M3 in Finland - Antti Ripatti (Bank of Finland, 1996)
We derive a theoretical model for the demand for money using the money-in-the-utility-function approach.The steady-state - utility function - parameters of the model of narrow money (Ml) estimated with cointegration techniques are stable over the foreign exchange rate regime shift; whereas in the model of harmonized M3 (M3H) they are not stable.The theoretical model fits the M1 data.The adjustment cost parameters of the M1 model describing the dynamics of the demand for money are stable over the sample period.The adjustment cost parameters of the M3H model are not stable.These results suggest that from the Finnish point of view Ml would be a more appropriate intermediate target for monetary policy than harmonized M3.
URN:NBN:fi:bof-20140807604
Keywords: 330; money-in-the-utility-function model - structural breaks - demand for money - narrow money - harmonized M3